PANDANGAN ULAMA ACEH TERHADAP HUKUMAN CAMBUK DI PENJARA - Faizin, Darul (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2021)
In 2018 the Governor of Aceh issued Pergub Aceh No. 5 of 2018. The case became a controversy in the community because one of its rules stated that whipping was carried out in prison. The pergub became a discussion of the community, not except the ulema. Therefore, the author was interested in compequesting the Aceh ulema view of the punishment of whipping in prison. The results showed that dayah ulema more agreed that whipping punishment is done in public places because it is considered to have run well, easily accessible to the public, and more effective for learning. While there are campus ulema who agree that whipping is carried out in prison because it is considered not contrary to Islamic law, more controlled, and more politically correct, but there are also campus ulema who do not agree because it is considered to eliminate the value of learning for the community. The difference arises because of different points of view; clerics who do not agree the punishment of whipping is carried out in prison more see the effectiveness, while the clerics who agree to see normatively and politically.